If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + 19t + -5 = 9t + 62 + -2t Reorder the terms: 7 + -5 + 19t = 9t + 62 + -2t Combine like terms: 7 + -5 = 2 2 + 19t = 9t + 62 + -2t Reorder the terms: 2 + 19t = 62 + 9t + -2t Combine like terms: 9t + -2t = 7t 2 + 19t = 62 + 7t Solving 2 + 19t = 62 + 7t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-7t' to each side of the equation. 2 + 19t + -7t = 62 + 7t + -7t Combine like terms: 19t + -7t = 12t 2 + 12t = 62 + 7t + -7t Combine like terms: 7t + -7t = 0 2 + 12t = 62 + 0 2 + 12t = 62 Add '-2' to each side of the equation. 2 + -2 + 12t = 62 + -2 Combine like terms: 2 + -2 = 0 0 + 12t = 62 + -2 12t = 62 + -2 Combine like terms: 62 + -2 = 60 12t = 60 Divide each side by '12'. t = 5 Simplifying t = 5
| 10x+4=5+2x | | 5(-6+4h)= | | 4x+13y=60 | | -2k-4-5+6k= | | -4(7p+9)= | | 5x=14.5 | | (Z/8)=-30 | | 5x+12=78 | | -9-8p+5+3p= | | 7y-2y= | | 6r=-42 | | 5d+9+2d= | | 3.6q-2.9-5.6q=-3.0q-4.2 | | (6)x=10 | | 6k+4-7k= | | (2x)(3x)=384 | | 6*(2/3)^2+11*(2/3)-10=0 | | -7y+8=-8y+2 | | 6(4x-8)=3(8x+7) | | 10(t-4)+4t=7(2t+2)-12 | | 9+7r-7=9r+6-3r | | 9x^2=17-6x | | 9+7r-7=6-3r | | v^2-8v+91=0 | | 9-4w=-3 | | 7x+6y=-8 | | x-18=-24 | | 3n+4n=21 | | 8=x^2+12x | | (z/14)=-19 | | c^2-2cd+d^2=0 | | -8.5x=68 |